BUSINESS DEVELOPMENT BASED ON VOICE OF CUSTOMER SYSTEM TO IMPROVE SERVICE QUALITY IN CULINARY BUSINESSES - Julita Nanna; Muhammad Rakib; Agus Syam (JIEKA: Jurnal Integrasi Ekonomi, Keuangan, dan Akuntansi, 2025)
This research aims to improve the quality of service in the culinary business (Business "Ayam Krispi Athiyyah") through the implementation of the Voice of Customer system. This research uses the comprehensive ADDIE development model. Data were collected through interviews, surveys, and online suggestion boxes based on barcodes. The research results show that the implementation of the Voice of Customer significantly improves customer satisfaction through quick responses to complaints, timely service, and consistent service quality. The online suggestion box barcode system facilitates real-time collection of customer feedback, supports data-driven decision-making, and provides opportunities for continuous improvement. Additionally, the application of the ADDIE model has proven effective in designing solutions that are relevant and aligned with customer needs. This study provides practical contributions for micro-enterprises to enhance competitiveness through customer-based service innovations.